Single-Cell Sequencing on Marine Life: Application and Future Development - Li, Jing; Wang, Hao; Li, Chaolun (Frontiers in Marine Science, 2022)
Single-cell RNA-sequencing (scRNA-seq) is the genomic approach that directly examines gene expression information from individual cells and provides a higher resolution of cellular differences than bulk RNA-seq. In the past decade, with the rapid development of microfluid, barcoding, and next-generation sequencing (NGS) technologies, scRNA-seq has revolutionized transcriptomic studies and gained great success and broad prospects. However, compared with the wide use in the few model animals, the application of scRNA-seq in marine organisms is limited due to the high cost of early scRNA-seq and the immature of single-cell methods for marine organisms. Recently, with the increase of genomic data, maturation of scRNA-seq platform and downstream bioinformatics algorithms, the scRNA-seq has been successfully applied in several marine model animals with great success, which demonstrated that the scRNA-seq could be the ideal and powerful tool to extend our understanding of marine organisms’ evolutionary and physiological processes and their adaptation to ecological niches. Here, we review the state-of-the-art improvements of single-cell sequencing techniques and new studies that apply single-cell methods to marine organisms. We also summarize the opportunities and challenges scientists may face in further single-cell research and propose several appealing prospects that may benefit from the combination of single-cell techniques and marine organisms.